Bank Losses, Monetary Policy and Financial Stability-Evidence on the Interplay from Panel Data - Zicchino, Lea.; Nier, Erlend (Washington, D.C. : International Monetary Fund, 2008)
We assess the extent to which loan losses affect banks' provision of credit to companies and households and examine how feedback from losses to a reduction in credit is affected by the monetary policy stance. Using a unique cross-country dataset of more than 600 banks from 32 countries, we find that losses lead to a reduction in credit and that this effect is more pronounced when either initial bank capitalization is thin or when monetary policy is tight. Moreover, in the face of credit losses, ample capital is more important in cushioning the effect of loan losses when monetary policy is tight. In other words, capital buffers and accommodating monetary policy act as substitutes in offsetting the adverse effect of losses on loan growth. While most of these effects are stronger in crisis times, we find them to operate both in and outside full-blown banking crises. These findings have important implications for the interplay between financial stability and monetary policy, which this paper also draws out.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet